Integrasi Penilaian Skor Risiko Stroke dan Konseling untuk Pencegahan Stroke yang Efektif - Luh Ade Wilan Krisna; Burhannuddin Burhannuddin; Cokorda Dewi Widhya Hana Sundari; Agus Antara; Kadek Surya Hendrawan; Komang Ayu Aishvarya Gangga Devi; Anak Agung Sri Septyari; Ni Putu Kawitana Ayuniari; Ni Kadek Premananda Maharani (Pusat Publikasi ITS, 2026)
Stroke is a brain dysfunction with various clinical manifestations that occurs suddenly due to impaired cerebral blood circulation. In Indonesia, stroke remains the leading cause of death and disability with an increasing prevalence. Promotive and preventive efforts are a priority to reduce morbidity, disability, and mortality due to stroke. This community service activity is a promotional intervention in the form of counseling and education about stroke and a preventive intervention in the form of screening for stroke risk factors in the elderly community. Screening was conducted for eight stroke risk factors, including blood pressure, heart rhythm, smoking status, cholesterol levels, diabetes mellitus, physical activity, body mass index, and family history of stroke. The activity was attended by 40 elderly people, consisting of 20 men (50%) and 20 women (50%). Based on the total stroke risk score, 20 people (36.4%) had a high risk of stroke, 29 people (52.9%) had a moderate risk of stroke, and 6 people (10.9%) had a low risk of stroke. The total number of participants with moderate to high risk reached 89.1%. The group with moderate to high risk requires follow-up and risk factor therapy to prevent future stroke events. The stroke risk card in this activity is expected to be used more widely in various health facilities and communities as a screening and education tool.